Laying the foundations of a culture of health as a pedagogical problem - Khalajtsan, A.P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to show the dominant influence of educational - educational process lay the groundwork for a culture of health students. Material : processed more than 40 references, conducted a survey, questionnaires and observation of the living conditions of students. Results : named main reasons for creating a culture of health of students should be considered as primary pedagogical problem. The preconditions and conditions of the foundations of the culture of youth health, namely: social, educational, health, environmental, economic, geographic, individual. Traced the sequence and phasing of the pedagogical process of building a culture of health of students in the course of many years of teaching in higher education. Conclusions : proven pedagogical influence priority basis forming a culture of health of students in the individual development and identity formation for learning in higher education. The sequence and structure of the solution of pedagogical problems of forming the foundations of a culture of health students.